(untitled) - Jain, Ravi (Hoboken, N.J., 2005)
One of the key characteristics of the next generation of communications networks is that they will be open for software vendors to create services for customers. These services will hinge on the development of flexible application programming interfaces (APIs) for call control. This book examines next generation APIs, emphasizing Java Call Control throughout. Readers will also find valuable insights into the pros and cons of various call control models.
Keywords: Telephone systems,Cell phone systems,Internet telephony,Convergence (Telecommunication); Data processing,Data processing